The Secondary Scintillation Output of Xenon in a Uniform Field Gas Proportional Scintillation Counter - Conde, C. A. N. (1977)
Data an the xenon uniform field gas proportional scintillation counter is presented. The energy resolution obtained for 8.1 MeV a-particles was 1.2%. Measurements for pressures from 600 to 1500 Torr showed that the "reduced light output", i. e. the number of photons produced by a single electron travelling the unit of distance, divided by the gas pressure, depends only on the reduced electric field but not on the gas pressure. An empirical equation for this quantity is given. The role played by different mechanisms is discussed